Filsafat Ilmu Indonesia: Kontribusi Berkelanjutan terhadap Pengembangan Ilmu Pengetahuan - Fahrurrozhi, Alfian; Kurnia, Heri (Academy of Social Science and Global Citizenship Journal, 2022)
This article provides a brief overview of the development of philosophy of science in Indonesia, highlighting the unique and original contributions of Indonesian philosophers and scientists in expanding insights and understanding of science. By bridging the gap between Western philosophical traditions and local cultural contexts, they have enriched the theories and methodologies of the philosophy of science and made significant impacts on societal development and educational improvement in Indonesia. This research employs a descriptive literature-based research method with specific analysis and criteria. The results indicate the development of local epistemology, critical thinking towards Western knowledge, the development of local concepts, reflection on the social and environmental implications of science, dialogue between science and religion/culture, as well as critical studies of technology and innovation. In conclusion, this article emphasizes the importance of the complementary relationship between philosophy and science in the pursuit of deeper knowledge and wisdom, and in leading a responsible life.